Lymphatic markers in the human optic nerve. (August 2018) - Trost, A.; Runge, C.; Bruckner, D.; Kaser-Eichberger, A.; Bogner, B.; Strohmaier, C.; Reitsamer, H.A.; Schroedl, F.
Abstract: Tissues of the central nervous system (CNS), including the optic nerve (ON), are considered a-lymphatic. However, lymphatic structures have been described in the dura mater of human ON sheaths. Since it is known that lymphatic markers are also expressed by single non-lymphatic cells, these results need confirmation according to the consensus statement for the use of lymphatic markers in ophthalmologic research. The aim of this study was to screen for the presence of lymphatic structures in the adult human ON using a combination of four lymphatic markers. Cross and longitudinal cryo-sections of human optic nerve tissue (n = 12, male and female, postmortem time = 15.8 ± 5.5 h, age = 66.5 ± 13.8 years), were obtained from cornea donors of the Salzburg eye bank, and analyzed using immunofluorescence with the following markers: FOXC2, CCL21, LYVE-1 and podoplanin (PDPN; lymphatic markers), Iba1 (microglia), CD68 (macrophages), CD31 (endothelial cell, EC), NF200 (neurofilament), as well as GFAP (astrocytes). Human skin sections served as positive controls and confocal microscopy in single optical section mode was used for documentation. In human skin, lymphatic structures were detected, showing a co-localization of LYVE-1/PDPN/FOXC2 and CCL21/LYVE-1. In the human ON however, single LYVE-1+ cells were detected, but were not co-localized with any other lymphatic marker tested. Instead, LYVE-1+ cells displayed immunopositivity for Iba1 and CD68, being more pronounced in the periphery of the ON than in the central region. However, Iba1+/LYVE-1- cells outnumbered Iba1+/LYVE-1+ cells. PDPN, revealed faint labeling in human ON tissue despite strong immunoreactivity in rat ON controls, showing co-localization with GFAP in the periphery. In addition, pronounced autofluorescent dots were detected in the ON, showing inter-individual differences in numbers. In the adult human ON no lymphatic structures were detected, although distinct lymphatic structures were identified in human skin tissue by co-localization of four lymphatic markers. However, single LYVE-1+ cells, also positive for Iba1 and CD68 were present, indicating LYVE-1+ macrophages. Inter-individual differences in the number of LYVE-1+ as well as Iba1+ cells were obvious within the ONs, most likely resulting from diverse medical histories of the donors. Highlights: Absence of lymphatic markers in human optic nerve (ON). Absence of lymphatic markers in human dura mater. Presence of LYVE-1 positive macrophages in the ON and surrounding tissue.